2020
DOI: 10.1016/j.ijedro.2020.100011
|View full text |Cite
|
Sign up to set email alerts
|

College students’ use and acceptance of emergency online learning due to COVID-19

Abstract: Due to COVID-19, higher education institutions transitioned to online learning. This study explored college students’ perceptions of their adoption, use, and acceptance of emergency online learning. The factors analyzed were attitude, affect, and motivation; perceived behavioral control (ease of use of technology, self-efficacy, and accessibility), and cognitive engagement. Quantitative and qualitative data were collected from 270 students. The findings present how motivation, self-efficacy, and use of technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
607
1
34

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 782 publications
(672 citation statements)
references
References 22 publications
30
607
1
34
Order By: Relevance
“…Therefore, from measuring the Likert scale of a questionnaire involving 8 core drives, it has been found that the motivational drive of 8 core drives is "high". Even though the research [3] has stated that students prefer traditional learning, the results of this study indicate that there is considerable potential to optimize online learning.…”
Section: A Analyzing Results Measurement Of Likert Scalementioning
confidence: 63%
See 3 more Smart Citations
“…Therefore, from measuring the Likert scale of a questionnaire involving 8 core drives, it has been found that the motivational drive of 8 core drives is "high". Even though the research [3] has stated that students prefer traditional learning, the results of this study indicate that there is considerable potential to optimize online learning.…”
Section: A Analyzing Results Measurement Of Likert Scalementioning
confidence: 63%
“…During the Covid-19 pandemic, the learning process in all countries was carried out using an online system [1], [2], [3]. At least, some fundamental problems affect the success of online learning, especially in the Covid-19 pandemic, one of them is the problem of limited infrastructure [2], [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussing the results obtained, it can be assumed that in the situation of forced distance learning during the summer session, the system of personal senses and related actual psychoemotional states affects the activity of the zone of singularity of sense and undergoes a change, subjectively perceived as tension and mental activation. Continuing the discussion, according to studies, as a result of depletion of resources, especially in connection with the efforts made to volitional control over the situation, the ability to psychological well-being and self-regulation is significantly reduced [5,16,17,19]. Table 3 below shows the results of the correlation analysis.…”
Section: Key Results and Discussionmentioning
confidence: 96%